2019
DOI: 10.1590/1982-4327e2912
|View full text |Cite
|
Sign up to set email alerts
|

Learning of Pseudowords by Children of Different Ages in a Shared Book Reading Context

Abstract: Shared book reading favors incidental learning of vocabulary; however, studies indicate that the previous vocabulary level of the child interferes with learning. The aim of this study was to compare the learning relations between pseudowords and figures of children aged 3 and 7 years in a shared book reading situation and to investigate the possible occurrence of the Matthew Effect. A book with four pseudowords developed for this study was read three consecutive times to 10 children of each age group. Matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This result may indicate that implicit vocabulary teaching through story reading is efficient depending on the number of unknown word-picture relations. Vaz and Schmidt (2019) have shown that teaching four new word-picture relations through reading books is very difficult, even for older children (aged 7 years). The results discussed here suggest that the learning of two new relations is similar under explicit and implicit teaching conditions; however, a larger number of relations may require explicit teaching strategies, such as auditory-visual pairing, for example.…”
Section: Discussionmentioning
confidence: 99%
“…This result may indicate that implicit vocabulary teaching through story reading is efficient depending on the number of unknown word-picture relations. Vaz and Schmidt (2019) have shown that teaching four new word-picture relations through reading books is very difficult, even for older children (aged 7 years). The results discussed here suggest that the learning of two new relations is similar under explicit and implicit teaching conditions; however, a larger number of relations may require explicit teaching strategies, such as auditory-visual pairing, for example.…”
Section: Discussionmentioning
confidence: 99%